Cyanobacterial sigma factors: Current and future applications for biotechnological advances - Srivastava, Amit; Summers, Michael L; Sobotka, Roman (Biotechnology advances, 2020)
A sigma (σ) factor is a constituent of bacterial RNA polymerase that guides the holoenzyme to promoter sequences and initiates transcription. In addition to a primary housekeeping σ factor, bacteria contain a number of alternative σ factors which recognize a specific set of promoters. By replacing the primary σ factor with alternative variants, the cell controls transcription of the whole sets of genes, typically to acclimate to changes in the environment. As key regulatory elements, σ factors are frequent targets of genetic manipulation aimed at the improvement of bacterial stress tolerance and capacity for bioproduction. Cyanobacteria are a phylum of bacteria capable of oxygenic photosynthesis and there is a great interest to employ them as biochemical and biofuel production hosts. Engineering of σ factor genes has become an important strategy to improve robustness and suitability of cyanobacteria for the production of high-value metabolites such as polyhydroxybutyrate, succinate, sucrose or hydrogen. Here, we summarize the current knowledge about the regulatory role of different σ factor classes in cyanobacteria, highlighting their biotechnological potential.
Keywords: sinice; DNA řízené RNA-polymerasy; RNA polymerase; Cyanobacteria; Sigma Factor; Anabaena; Environmental stress; Transcription, Genetic; fotosyntéza; genetická transkripce; DNA-Directed RNA Polymerases; Bacterial Proteins; Biofuel; Sigma factor; sigma faktor; Photosynthesis; Metabolites; Synechocystis; bakteriální proteiny